Two-temperature model of gas combustion in a model burn device of the cylindrical form; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Knyazeva A. G. Anna Georgievna (Power engineering, 2007)
Заглавие с титульного листа